Perilaku Individu dalam Berzakat: Pengaruh Income dan Elastisitasnya - Maulana, Rizky (Prodi Ekonomi Syariah Pascasarjana IAIN Kudus, 2020)
This study aims to look at the effect of income on individual behavior in paying zakat and its elasticity. Zakat is an Islamic obligation, but there are still high-income individuals who still do not pay zakat. This research uses the probit regression method to observe individual behavior in paying zakat, while to examine the elasticity, a simple linear regression method was used. The results obtained from the probit regression are income variables do not affect the individual decision in paying zakat, while the education, religiosity, homeownership status and loan variables were significant toward an individual decision in paying zakat. The result of a simple linear regression with a natural logarithmic model shows that the relationship of income with the amount of zakat was inelastic. That is, the percentage increase in the amount of zakat is less than the percentage increase in income.